2018
DOI: 10.3171/2017.7.peds17317
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations for abuse in young children with subdural hemorrhages: findings based on symptom severity and benign enlargement of the subarachnoid spaces

Abstract: OBJECTIVEChildren who have subdural hematomas (SDHs) with no or minimal neurological symptoms (SDH-mild symptoms) often present a forensic challenge. Nonabusive causes of SDH, including birth-related SDH, benign enlargement of the subarachnoid spaces (BESS), and other proposed causes have been offered as etiologies. These alternative causes do not provide explanations for concomitant suspicious injuries (CSIs). If SDH with mild symptoms in young children are frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…Accidental trauma or abuse was reported in 5/12 (41.7%) of subdural collections which were hemorrhagic. Besides, up to 50% of children with BESS and SDH may display concomitant important injuries [167].…”
Section: Subdural Hematoma In the Setting Of Benign Enlargement Of Thmentioning
confidence: 99%
“…Accidental trauma or abuse was reported in 5/12 (41.7%) of subdural collections which were hemorrhagic. Besides, up to 50% of children with BESS and SDH may display concomitant important injuries [167].…”
Section: Subdural Hematoma In the Setting Of Benign Enlargement Of Thmentioning
confidence: 99%
“…Triaden består av tre medisinske funn: subduralt hematom, utbredte øyebunnsblødninger og encefalopati. Min erfaring, og også vist i litteraturen (2,3), er at encefalopati ikke lenger er nødvendig for diagnosen «shaken baby». Kombinasjonen av subduralt hematom og øyebunnsblødninger synes tilstrekkelig.…”
Section: Triadenunclassified
“…Disagreement still exists as to whether BEH is a risk factor or not. 76,77 A recent review investigated the similarities between SDH and BEH, and presented a unifying theory of pathophysiology behind these subdural collections 78 Few neuroimaging studies have reported findings of ruptured bridging veins, except the ones reviewed above. Findings such as the tadpole or lollipop signs lack pathologic verification of bridging vein injuries.…”
Section: Discussionmentioning
confidence: 99%